Protesi di rivestimento e stemless in chirurgia della spalla. Indicazioni, limiti e prospettive - Bove, A.; Cozzolino, A.; Soldati, A.; Matino, G.; Del Regno, N. (Lo Scalpello - Journal, 2019)
RESURFACING AND STEMLESS ARTHROPLASTY IN SHOULDER SURGERY. INDICATIONS, LIMITS ANDPERSPECTIVESSmall implants in shoulder replacement surgery represent a viable alternative to traditional surgery in specificconditions. Resurfacing and stemless implants have been introduced with the goal of preserving bone, reduce the riskof humeral periprosthetic fractures and simplify revision procedures. Clinical studies show very good clinical resultsand low complication rates in selected patients when correctly implanted. The use of small implants in shoulderreplacement surgery appears to be a viable option for shoulder replacement, especially in young patients, even thoughfuture studies are required to assess the long-term outcomes.